2010
DOI: 10.1021/bi9020296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interdomain Tether Length and Flexibility on the Kinetics of Intramolecular Electron Transfer in Human Sulfite Oxidase

Abstract: Sulfite oxidase (SO) is a vitally important molybdenum enzyme that catalyzes the oxidation of toxic sulfite to sulfate. The proposed catalytic mechanism of vertebrate SO involves two intramolecular one-electron transfer (IET) steps from the molybdenum cofactor to the iron of the integral b-type heme and two intermolecular one-electron steps to exogenous cytochrome c. In the crystal structure of chicken SO (Kisker et al., Cell, 1997, 91, 973-983), which is highly homologous to human SO (HSO), the heme iron and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 63 publications
5
60
0
Order By: Relevance
“…The fact that the apo-heme domain also inhibits nitrite reduction, to some extent, suggests an important conformational component in the access of nitrite to sulfite-reduced SO. There is a flexible hinge (14 residues in human SO) that tethers N-terminal heme domain to Mo-domain (21). Previous studies have shown that this hinge controls domain motion during the catalytic cycle of SO, which adopts various conformations during intramolecular electron transfer (IET) and catalysis (49).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the apo-heme domain also inhibits nitrite reduction, to some extent, suggests an important conformational component in the access of nitrite to sulfite-reduced SO. There is a flexible hinge (14 residues in human SO) that tethers N-terminal heme domain to Mo-domain (21). Previous studies have shown that this hinge controls domain motion during the catalytic cycle of SO, which adopts various conformations during intramolecular electron transfer (IET) and catalysis (49).…”
Section: Discussionmentioning
confidence: 99%
“…11) using the nonlinear-least-squares fitting algorithm in the software program Origin © : Eapp=E0+2.303(RTnF)log10([Ox][Red]) where E app is the applied potential, E 0 is the midpoint potential determined from these data, and [Ox] and [Red] are, respectively, the concentrations of the Fe(III) and Fe(II) states of the b 5 heme of hSO. For a previous application of this method to hSO see Figure 4 of ref 17.…”
Section: Methodsmentioning
confidence: 99%
“…These mutations include: deletion of tether residues (17); mutation of the aromatic residues around both the heme and Mo domains (18, 19); mutation of conserved active site residues (20-22); and producing some of the fatal mutations (22-26) such as R160Q and K322R. Although many of these mutants have provided much insight into the structural and kinetic characteristics of hSO, some have shown unexplained or even paradoxical results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 In the family of cytochrome b 5 homologues, microsomal cytochrome b 5 itself is connected to its transmembrane segment by a flexible linker: the latter enables cytochrome b 5 to interact alternatively with its reductases and its diverse electron acceptors, all of them attached to the endoplasmic reticulum. 33,51 Sulfite oxidase is the system with most similarity to Fcb2, in that the b 5 -like heme domain is covalently attached to its reductase, a molybdopterin domain, and transfers electrons to cytochrome c. In this case, the crystal structure of the chicken liver enzyme is not considered as that of an electron transfercompetent complex, and the flexible peptide loop must allow the orientation changes necessary for shuttling electrons between the molybdopterin domain and cytochrome c. [52][53][54] In all structural and modeling studies with cytochrome b 5 mentioned above, the surface that interacts with electron acceptors is that around the exposed heme edge. Thus far, Fcb2 is the only system for which both crystallographic and functional details exist concerning the electron transfer-competent interaction of a b 5 -like cytochrome with its reductase, an interaction that again implicates the area around the exposed heme edge.…”
Section: Resultsmentioning
confidence: 99%